EFEKTIFITAS EMPAT SPESIES LEGUM SEBAGAI INANG ANTARA TANAMAN HEMI-PARASIT CENDANA (SANTALUM ALBUM L.) - Mangadas Lumban Gaol; Maria Longa Ruma (Environmental Research Center (PPLH) of Udayana University, 2009)
Research to investigate the effectively of four legume species as intermediate host of sandalwood was conducted. Research consist of five treatments; in four treatments, sandalwood was grown with C. siamea, A. leucophloea, A. farnesiana or A. villosa while in one experiment sandalwood was grown without host. Host treatment significanlty affected growth of sandawood. Based on sandalwood height, of four legumes used the best host for sandalwood was A. farnesiana. Host treatment also affected sandalwood biomass. Root, stem and leaf biomass of sandalwood grown with A. farnesiana were higher compare to grown with other host. Generally, based on sandalwood biomass, C. siamea did not affected growth of sandalwood while A. leuophloea and A. villosa tend to reduce growth of sandalwood. Number of leaf and leaf area were also different between treatments. The highest was in sandalwood grown with C. siamea and A. farnesiana while grown with other host were lower. Root length was marginally different between treatments. However, root of sandalwood grown with host was longer compare to sandalwood grown without host.